Differential scanning calorimetry as a fast method to discriminate cage or free-range rabbit meat. (October 2019) - Secci, Giulia; Ferraro, Giovanni; Fratini, Emiliano; Bovera, Fulvia; Parisi, Giuliana
Abstract: In this work, we proposed the use of differential scanning calorimetry (DSC) as a rapid tool for the discrimination of meat samples coming from free-ranged and caged rabbits. Fatty acid composition, colour, and texture were also provided to fully characterize meat quality of the different samples. A total of 36, thirty-seven days old California × New Zealand White male rabbits were divided into 2 groups, housed in open air cages and in ground free-range, respectively. After 62 days of farming, 12 rabbits per group were slaughtered and the skinned carcasses were chilled for 24 h at 4 °C prior to be dissected. The Longissimus thoracis et lumborum muscle was analysed. The overall fatty acid profile was not affected by the farming system, while free-range rabbits show a significant lower L* value (49.59) than the open-air ones (53.54). Nor a* and b* were altered. Texture measurements revealed that there was no effect of housing system on shear force. More interestingly, the deconvolution of DSC signals in the range 30–90 °C revealed that free-range rearing lead to an increase of myosin amount in meat, being its peak percentage equal to 8.5 ± 1.9 against 4.3 ± 2.2 in meat from caged rabbits. Highlights: Meat from free-ranged and caged rabbit meat was discriminated thanks to DSC . An increase of myosin amount in meat from free-ranged rabbit was observed. Meat lightness was affected by rearing conditions. Texture and fatty acid profile scarcely differentiate between farming systems.